Troble Maker Pada Anak PIAUD Dan Cara Menanganinya - Siti Mufarochah; Sonia Sonia (ZAHRA: Research and Tought Elementary School of Islam Journal, 2020)
Every child has a lot of extraordinary potential, depending on how the parents hone and nurture it. Children have various hopes and beauties in them, but children can turn into Troble Maker if wrong care, bad environmental conditions, experiences during developmental times, bad relationships between parents, materially incapacitated, lack of attention to children, poor communication, parents are too busy with work, too much physical and psychological punishment. There are ways to deal with the Troble Maker child are some of the approaches, methods and steps. The approaches used are the Rational Approach, Emotional Approach, Functional Approach, Behavioristic Approach, Cognitive Approach, Humanistic Approach. The method used is the Uswah method, the method of advice, the habituation method, the Shawab method and `Iqab, social skills. For the steps used are as follows: Step of Discovery, Step of Understanding, Step of Living, Step of Practice, Step of Consolidation.